On the microstructural origins of martensitic transformation arrest in a NiCoMnIn magnetic shape memory alloy. (1st January 2018) - Bruno, N.M.; Salas, D.; Wang, S.; Roshchin, Igor V.; Santamarta, R.; Arroyave, R.; Duong, T.; Chumlyakov, Y.I.; Karaman, I.
Abstract: The martensitic transformation arrest phenomenon in Ni45 Co5 Mn36.6 In13.4 meta-magnetic shape memory alloy (MMSMA) single crystals was investigated as a function of secondary annealing heat treatments, using thermo-magnetometry and transmission electron microscopy (TEM). Dark-field images of the austenite phase at room temperature revealed the long range L21 and B2 ordered microstructural landscape with different morphologies in the annealed single crystals. Their measured thermomagnetic responses demonstrated full transformation arrest after certain heat treatments and unique microstructural morphologies. Martensitic transformation hysteresis, range, and enthalpy were measured in the annealed partially- or non-arrested single crystals. With the data, herein, we found that the samples with long range L21 ordering exhibit martensitic transformation at higher temperatures than some of the crystals of the same composition showing predominantly B2 order. This finding opposes the previous reports on the effect of annealing on the martensitic transformation characteristics of MMSMAs. We provide evidence that long range order promoted with high temperature annealing is not the only microstructural feature capable of influencing the martensitic transition in NiCoMnIn MMSMAs. Data suggests that quenched in vacancies, in addition to long range order, also influence the transformation characteristics. Graphical abstract: Image 1